In vitro evaluation of resistance of potato cultivars to Phytophthora infestans - Cristinzio, G.; Testa, A.
The resistance of ten potato cultivars (Agria, Ajax, D6sir~e, Liseta. Kennebec, Majestic. Monalisa, Prima, Spunta and Tonda di Berlino)to Phytophthora infestans was analyzed in vitro using 8 fungal strains. An assay based on electrolyte leakage was used for screening leaves and tuber tissues with fungal culture filtrates. With almost all cultivars the resistance of leaves did not correlate with the resistance of tubers. Cv. Ajax appeared the least susceptible in both leaf and tuber tests, while the cv. Prima was the most susceptible in tuber tests.
Keywords: LATE BLIGHT; TESTING METHODS; ELECTROLYTE LEAKAGE; SOLANUM TUBEROSUM L